A new technology for resolving the dynamics of a swinging bat - King, K.; Hough, J.; McGinnis, R.; Perkins, N. C. (Sports Engineering, 2012)
Hitting a major league fastball, with approximately half a second to react, poses one of the greatest challenges in sports. The ability to hit the ball derives from the dynamics of the bat swing which can be measured using video motion capture. However, doing so necessitates swinging the bat within the confines of a motion capture laboratory, often with considerable time and expense. This paper introduces an inexpensive and highly portable measurement method for use right on the field of play to support player training, coaching, rehabilitation, and player-bat fitting. The method employs a highly miniaturized, wireless MEMS inertial measurement unit (IMU) affixed to the knob of the bat. The IMU incorporates three-axis sensing of bat acceleration and angular velocity with a low-power RF transceiver to transmit this data to a host computer. Analysis of this data yields a near-instantaneous and highly resolved summary of three-dimensional bat dynamics. This paper describes this novel technology for use in baseball and softball, presents example results, and reveals new features of bat motion overlooked in previous studies.